Reviews of recent publications (Studies in 20th & 21st Century Literature, 2005)
Edwards, Catherine, ed. Roman Presences: Receptions of Rome in European Culture, 1789-1945. Christina Ujma Gilman, Sander L. and Jurek Becker. A Life in Five Worlds. David Malcolm Rodden, John, ed. Conversations with Isabel Allende. Daniela Melis Schrift, Alan D., ed. Why Nietzsche Still? Reflections on Drama, Culture, and Politics. Jennifer Marston William Viegnes, Michel, ed. Hugo et la chimère. Recherches & Travaux 62. Kathryn M. Grossman Winston, Jane Bradley. Postcolonial Duras: Cultural Memory in Postwar France. Carol J. Murphy
Keywords: Catherine Edwards; Roman Presences: Receptions of Rome in European Culture 1789-1945; Christina Ujma; Sander L. Gilman; Jurek Becker; A Life in Five Worlds; David Malcolm; John Rodden; Conversations with Isabel Allende; Daniela Melis; Alan D. Schrift; Why Nietzsche Still? Reflections on Drama Culture and Politics; Jennifer Marston William; Michel Viegnes; Hugo et la chimère; Recherches & Travaux 62; Kathryn M. Grossman; Jane Bradley Winston; Postcolonial Duras: Cultural Memory in Postwar France; Carol J. Murphy